(MAIL) ART AS PROCESS (Palíndromo, 2016)
Just like any cultural expression, mail art arises, internationally, from dif- ferent influences and questions that are legacy of prior or contemporary situa- tions. In this article I present some of the- se influences, at least the main, as well as an overview of the artistic and historical context that fed this practice. Starting with issues of the conceptual art and the conceptualists manifestations that oc- curred in Latin América, I relate mail art to this series of artistic proposals that had as main issue the “art object”, the criticism to museum institutions and the place of art in life. Understanding mail art in its in- ternational dimension, finally, I place this practice in the Brazilian artistic context, for which I have particular interest, from the mapping of events and subsequently its recent institutionalization.
Keywords: mail art; contemporary art; art instituonalization